Romania Climate Change and Low Carbon Green Growth Program - World Bank (Washington, DC, 2015)
This report has been prepared by the World Bank for the Government of Romania as an output of the World Bank advisory services program on climate change and low-carbon green growth in Romania. In response to the request, the World Bank quickly mobilized a team of sectoral and climate change (CC) specialists and conducted rapid assessments in six sectors - energy, transport, urban, water, agriculture, and forestry, which were pre-identified by both the Government of Romania and the World Bank as areas significant to emission mitigation and or adaptation to CC. The objective of rapid assessments was to quickly evaluate climate risks and identify CC-related investment priorities and necessary implementation support for the 2014-2020 operational programs. This document is the stocktaking report of component A1. It provides an introductory cover to the literature on CC, baseline for Romania, institutional review of Romania and key European Union (EU) requirements, as well as available data sets that were identified in the given short-time span. Its purpose is to support the government as a first stock of key climate and green growth issues for Romania and summarize the current situation. The report is structured as follows: section one gives introduction, section two provides the sectoral summary on the country background and characteristics. Section three provides the baseline for the CC and green growth challenges in Romania. Relevant climate dimensions of Europe 2020 and existing EU regulations and policies related to climate change are summarized in section four. Section five provides an overview of national strategies, regulatory framework, and organizational setup for addressing CC in Romania. Background information on the Romania 2014-2020 European structural and investment funds (ESIF) programming and CC related aspects in the forthcoming ESIF programming report are covered in section six. Finally, section seven provides a CC relevant bibliography for Romania that may serve as a tool for referring to key literature in the field.